Metodología de Reggio Emilia para Fortalecer los Aprendizajes Remotos en el Nivel Inicial 2 - Cahuasqui Garcés, Cristina Elizabeth (2022)
The present investigation strengthened the creativity in the teachers of the Initial Level 2 of the Educational Unit "Gral. Eloy Alfaro Delgado” from the city of Ambato, with a development of successful remote learning, which was carried out due to the Covid-19 pandemic. The use of sensory, exploratory and audiovisual resources and materials allows the motivation of the child to explore and know to get to obtain significant learning, which arise from environmental resources and the involvement of families, to generate affective ties in all the environments that the child develops, in this way, their diversity and their way of expressing themselves is accepted; The purpose of this work seeks to provide teachers with different strategies and resources that, when used, strengthen learning, criticality and autonomy of infants from the thought of Loris Malaguzzi